Theoretical model of restoring bending moment of Zhutou Puzuo based on deformation patterns with emphasize on rotation and interlayer sliding - Junxiao He; Wenyi Yang; Linlin Xie; Jingshu Wu (Journal of Wood Science)
Abstract The load-bearing capacity of Zhutou Puzuo in ancient timber structures is the crucial factor affecting the structural behaviors of the entire structure. The deformation pattern is the basis of the theoretical analysis of the bending moment of this component. However, the influence of deformation pattern on such moment has been rarely investigated. Both global and local deformation patterns associated with the structural behaviors of Zhutou Puzuo were herein investigated. The positions of original and maximum sliding during loading were identified and analyzed. The criterion for determining the uplift of Zhutou Puzuo was established. The theoretical model of Zhutou Puzuo emphasizing rotation and interlayer sliding based on deformation patterns was proposed and verified against experimental data. These results provided an important reference for the evaluation of load-bearing capacity of Zhutou Puzuo in ancient timber structures.